Transformasi cerpen Jendela Rara ke film Rumah Tanpa Jendela menggunakan kajian struktural - Dila Apriyanti; Esa Hilma; Dian Hartati (Aksara: Jurnal Bahasa dan Sastra, 2021)
Short story is a literary work that serves either to assist for entertaining or to give life values of the story itself. Besides, it is known as a prose work due to having a short-term story. The two short stories entitled “Jendela Rara'' and “Rumah Tanpa Jendela”, written by Asma Nadia, attracted the author's attention to conduct recent study towards those works. They have been adapted from short story to movie, hence, readers can obtain a structural comparison, especially intrinsic values and life values that are contained in the stories. The recent study was designed by using descriptive qualitative with structural approach to describe intrinsic elements that form the literary work. The research data was in quotation form (word, phrase, and sentence) which related to the problems of “Jendela Rara'' short story. The data collected were from document analysis technique. The data analyzed by using a flow technique model which consisted of three elements such as, data reduction, data presentation, and conclusion verification. The data result formed as a structural analysis while experiencing a transformation from a short story entitled “Jendela Rara” to a movie entitled “Rumah Tanpa Jendela” by Asma Nadia.Keywords: Short story, structural, transformation, Asma Nadia.